Study on the pathways of the reaction of ketenyl radicals and nitrogen dioxide (HCCO+NO2) - Thiem, Lam Ngoc; Hien, Mai Thu; Lam, Nguyen Thanh; A. Carl, Shaun; Tho, Nguyen Minh (Vietnam Journal of Chemistry, 2014)
Using the G3B3 method, we constructed the portions of potential energy surface containing low-energy pathways of HCCO + NO2reaction. These show that only two separate reaction pathways are possible leading to HCNO + CO2and HCO + NO + CO.